Common-sense and self-regulation model-based intervention to increase adherence and asthma control - Lugo González, Isaías Vicente (2024)
Objective. The effects of a common-sense and self-regulation model-based intervention to increase adherence behaviors and asthma control were valuated. Method. We tested an A-B and follow-up design, replicating the intervention with five women, ages between 25 and 55. The treatment was applied over three 90-minute sessions based on the following strategies: psychoeducation, reattribution, problem-solving, and objective feedback. Effects were assessed with standardized and behavioral measures of adherence, asthma control and pulmonary obstruction measurement over a period of 28-75 days, using visual analysis, effect size and clinical significance. Results. The increase in adherence behaviors for phase B and follow-up had a moderate-strong effect (NAP = .86-1, p < .01). In the case of asthma control, there were significant clinical effects (RCI = 2.32-5.42), as well as in pulmonary obstruction where patients decreased it between 11%-40%.